Progressive Detoriating Effect of Glucocorticoidson the Histomorphology of Seminiferous Tubules and Height of Germinal Epithelium of Testis of Albino Rats used for a Short Duration - Uzma Hameed, Sadia Iqbal, Urooj Fatima, Tanzeela Khan, Hira Ahmed, Shazia Fahmi, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective:To observe the microscopic changes in the seminiferous tubules of testis of albino rats, following the intravenous administration of corticosteroids. Study design: Laboratory based experimental study. Place and duration of the study: This study was conducted in the department of Anatomy, Baqai Medical University Karachi, in June 2017 for aperiod of 21 days. Methodology:32 Adult,healthy male Albino rats equally divided into four groups were used in this study.Group A1 served as control for group B1 and received intra-peritoneal injection of 0.9 % normal saline for 7 days, Group A2 served as control for group B2 and received i.p injection 0.9 %normal saline for 14 days, whereas Group B2 and Group B3 were given i.pinjection of Dexamethsone at the dose of 7mg/kg/body weight for 7 and 14 days in a single daily doseat the lower site of the abdomen respectively. Results:The Haematoxylin and Eosin (H&E) stained sections of testis tissue have shown marked histomorphological changes,the germinal epithelium was disorganized and there was a marked reduction in the height of epithelium Seminiferous tubules attained different shapes, congested blood vessels were also found,detachment and vacuolization of the seminiferous tubules were noted that eventually leads to atropy of the tubules. Conclusion:Even short term used of glucocorticoids caused changes in the histomorphology of seminiferous tubules that may lead to infertility.